Cardiovascular effects of immunosuppression agents - Elezaby, Aly; Dexheimer, Ryan; Sallam, Karim (Frontiers in Cardiovascular Medicine, 2022)
Immunosuppressive medications are widely used to treat patients with neoplasms, autoimmune conditions and solid organ transplants. Key drug classes, namely calcineurin inhibitors, mammalian target of rapamycin (mTOR) inhibitors, and purine synthesis inhibitors, have direct effects on the structure and function of the heart and vascular system. In the heart, immunosuppressive agents modulate cardiac hypertrophy, mitochondrial function, and arrhythmia risk, while in vasculature, they influence vessel remodeling, circulating lipids, and blood pressure. The aim of this review is to present the preclinical and clinical literature examining the cardiovascular effects of immunosuppressive agents, with a specific focus on cyclosporine, tacrolimus, sirolimus, everolimus, mycophenolate, and azathioprine.